1977
DOI: 10.1104/pp.59.5.849
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Dehydrogenase Complex from Higher Plant Mitochondria and Proplastids: Kinetics

Abstract: be competitive with the substrate for that enzyme unless the central complexes are kinetically important, in which case they will be noncompetitive. This prediction has been confirmed for acetyl-CoA and NADH in the bovine kidney and pig heart complexes (7, 16). Other product inhibition patterns should be uncompetitive except for the interaction of one product and the substrate of the subsequent enzyme when it will be noncompetitive, if the reaction at that site is random sequential. In the mammalian complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
1

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 9 publications
2
24
1
Order By: Relevance
“…The values obtained were in the range of those previously reported for PDC from etiolated pea shoots (29) and mitochondrial PDCs from other plant sources (5,17,28). The K, value for NADH is substantially lower than the Km NAD suggesting that product inhibition is of regulatory significance.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…The values obtained were in the range of those previously reported for PDC from etiolated pea shoots (29) and mitochondrial PDCs from other plant sources (5,17,28). The K, value for NADH is substantially lower than the Km NAD suggesting that product inhibition is of regulatory significance.…”
Section: Resultssupporting
confidence: 66%
“…It has been shown that like all mitochondrial PDCs thus far examined, the pea leaf complex is regulated in part by covalent modification (18), and the PDC from etiolated pea tissues exhibits product inhibition (29). While the pea mitochondrial PDC is the most thoroughly studied plant PDC, there are some inconsistencies in the reported results.…”
contrasting
confidence: 41%
See 3 more Smart Citations